PENGEMBANGAN PENDIDIKAN LINGKUNGAN HIDUP PADA ANAK USIA DINI - Aris Slamet Widodo (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2018)
The objectives of this community service were to know the role of service for early childhoodeducation in terms of environmental education, to determine suitable method, and to draft materialsguide for environmental education as well as to improve the learners’ knowledge in terms ofenvironmental maintenance.The location of community service was determined purposively, they were Melati Sari playgrouplocated in Putat, Selopamioro Village, Imogiri District, Bantul Regency, representing schools ofchildhood education in woods-based area or remote (upstream) and Labschool of Rumah Citta located in Mantrijeron, Yogyakarta Municipality, representing schools of childhood education in city-based area or downtown (downstream). The event was conducted from May to August 2013. Methods used in the learning service of environmental education through the following stages: (1)Assessment, (2) workshop of drafting formulation of assistance program, (3) Assistance, (4)workshop of reconsidering the application guideline, and (5) dissemination and recommendation tostakeholders.The results of community service concluded that Melati Sari Playgroup of Selopamioro andLabschool of Rumah Citta had introduced environmental education; however, they had no learningguideline yet. Suitable learning methods for environmental education were story-telling, role-play, aswell asw giving tasks and practices.Learning guideline for environmental (loving woods) education for early childhood consisted ofmaterials: (1) trees as the producer of paper and tissue, (2) trees as the producer of oxygen and theabsorber of carbondioxide, (3) woods able to supply water, (4) woods animals as part of theecosystem, (5) recycling paper, and (6) the sorting of paper.The final community service results of applying the guide learning of environmental (loving woods)education were the fact that improved knowledge of mantaining environment could be done bysaving the woods; either by planting trees or reducing the use of products made from the woodsproducts.